Geofencing: Mobile Technology as a Health Promotion Tool to Raise Awareness of a Dental Clinic in Rural North Carolina. Issue 3 (5th August 2020) - Wright, Wanda G.; Rafferty, Ann P.; Winterbauer, Nancy; Locklear, Kayla; Tucker‐McLaughlin, Mary
Abstract: Purpose: The purpose of the study was to assess the use of geofence technology to raise awareness of a dental clinic in rural North Carolina. Methods: The catchment area of the dental clinic was defined by ZIP Codes. A geofence was identified, and cell phones within the perimeter were targeted for oral health message drops to occur over 3 months from April to June 2017. Surveys conducted twice, pre‐ and postintervention (message drop), evaluated change in community awareness of services available at the dental clinic. A cross‐sectional analysis was used to measure the effect of the exposure to the geofence technology in survey respondents. Findings: The survey included 200 participants (100 pre‐ and 100 postintervention). There were no significant differences in race or age for pre‐ and postintervention survey groups. The majority of respondents were American Indians (47.0% pre, 58.6% post) or black (28.8% pre, 25.5% post). There was a statistically significant improvement in awareness of the dental clinic ( P = .045) from pre‐ to postintervention. A significant increase was also observed in the question related to dental visits by the respondent or family member of the respondent (from 6.5% to 15.0%, P = .04). A more modest improvement was found in questions related to the cost of dental care, type of insurance accepted, and services provided. Conclusion: Geofencing has the potential to increase awareness of health care services and ultimately increase the number of patients receiving care.